An Experimental Investigation for Seepage-Induced Instability of Confined Broken Mudstones with Consideration of Mass Loss. (27th September 2017) - Wang, Luzhen; Chen, Zhanqing; Kong, Hailing
Abstract : To study and prevent water-mud-outburst disasters of tectonic fracture zones in geotechnical engineering, we tested seepage stability of confined broken mudstones with consideration of mass loss using syringe seepage method and a self-designed seepage testing system, obtained the variation laws of seepage instable duration, total mass loss, and mass loss rate of broken mudstones under different pressure gradients and Talbol power exponents (simplified as Talbol hereafter), and explained their instable seepage behaviors. The results showed that the mass loss is the internal cause of seepage-induced instability of broken rocks and pressure gradient is the external cause, and the persistent migration and loss of particles result in progressive failure process, while the large enough pressure gradient causes sudden overall instability. The seepage instable duration shortens with pressure gradient increasing, with the longest and shortest duration at Talbol of 0.5 and 0.1, respectively. In general, mass loss increases with pressure gradient increasing and with Talbol decreasing. Mass loss rate increases with pressure gradient increasing but shows no monotonic changes with Talbol. Their expressions can be used to establish dynamic model in the further seepage stability researches.